2019
DOI: 10.31557/apjcp.2019.20.10.3093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DPYD*9A, DPYD*6 and GSTP1 ile105val Genetic Polymorphisms on Capecitabine and Oxaliplatin (CAPOX) Associated Toxicities in Colorectal Cancer (CRC) Patients

Abstract: chemotherapeutic care for the treatment of colorectal cancer (CRC) in the last decade. CAPOX treatment was proven to be equivalent or non-inferior to standard regimens like FOLFOX and FOLFRI in the treatment of advanced and metastatic CRC (Pectasides et al., 2015; Guo et al., 2016; Sobrero et al., 2018) and preferred over its counterparts due to convenience in administration and easy management. (Wehler et al., 2012) However, CAPOX treatment was associated with several dose-limiting haematological and non-haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Significance: P < 0.05 are classified to not affect the DPD function in a clinically relevant manner in the context of 5-fluorouracil related toxicity [30]. Interestingly, in accordance with our results, recent reports have shown an association with severe toxicity and high levels of 5-FU post-treatment for DPYD-rs1801265 [92][93][94].…”
Section: Discussionsupporting
confidence: 90%
“…Significance: P < 0.05 are classified to not affect the DPD function in a clinically relevant manner in the context of 5-fluorouracil related toxicity [30]. Interestingly, in accordance with our results, recent reports have shown an association with severe toxicity and high levels of 5-FU post-treatment for DPYD-rs1801265 [92][93][94].…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Table 6, the pooling of Indian data of 5‐FU/capecitabine toxicity 11–16 with the present study showed a lack of association of rs1801265, rs1801159 and rs2297595 variants with FU‐mediated toxicity. The rs1801160, rs1801158 and rs3918290 variants showed a 1.88‐, 4.40‐ and 158.14‐fold increased risk for FU‐mediated toxicity in Indians.…”
Section: Resultssupporting
confidence: 44%
“…A few Indian studies have explored the association of DPYD variants with 5‐FU/capecitabine‐mediated toxicity 11–16,24 . Low DPYD expression was linked to unfavourable overall survival in colorectal cancer patients 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this association, one of the suggested limitations for the lack of association in clinical studies may be due to the linkage disequilibrium observed with c.496A>G (rs2297595) and c.1129-5923C>G (rs75017182) (two candidate markers known as risk allele for 5- FU toxicity) [ 63 ], so further evaluation of these variants in the context of clinical outcomes is suggested. In light of the fact that 19.4% of the Ecuadorian population is a carrier of the polymorphic allele, it is important to carry out future studies to evaluate the side effects in carriers of this variant, especially considering the recent reports on toxicity in oncology patients [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%